Learning style preference among non-science and technology (s&t) students on database management course - Amran, Noraizan; Saiful Bahry, Farrah Diana; Mohd Yusop, Zulkefli (2012)
The purpose of this study is to identify the preferred learning styles of non-Science and Technology (S&T) students on database management course, and to examine the differences of students' learning styles on gender, program and grade achievement. This study used Barsch Learning Style Inventory (BLSI) instrument to evaluate the preferred learning styles by the respondents. A group of 200 students from Faculty of Information Management, Universiti Teknologi MARA who registered Database Management System (IMS504) course in semester 2009/2010 have been identified to be the respondent of this study. The students have being asked to answer the 24 statements in BLSI instrument, at the beginning of the semester. Total of 122 valid responses were subjected to further quantitative analyses of the study. The findings indicate that the most preferred learning style by the students is Visual and the least preferred is Kinesthetic. It shows the same result to the both male and female students, in all programs of studies and for every grade achieved by the students. The finding will be useful to the curriculum designers, the instructors, the lecturers and the policy makers to assist them in education activities and designing the curriculum, and also provide the extension education as well as creating the need for further research in this area.